Preliminary report of the Japanese version of the International Olympic Committee Sport Mental Health Assessment Tool 1 - Yasutaka Ojio; Shin Kawamura; Masanori Horiguchi; Vincent Gouttebarge (Sports Psychiatry)
Abstract: Objective: The International Olympic Committee (IOC) Sport Mental Health Assessment Tool 1 (SMHAT-1) is an athlete-specific screening tool developed to identify mental health symptoms in elite athletes and potential need for referral to care. We aimed to report the prevalence using the Japanese version of the SMHAT-1 in a Japanese sport context. Methods: Web-based anonymous self-report data of 220 competing Japan Rugby Top League rugby players were analyzed. The players answered all screening questionnaires of the SMHAT-1 containing the assessment for multiple mental health symptoms for sport-related psychological distress (step 1), and the following specific symptoms (step2): anxiety, depression, sleep disturbance, alcohol misuse, substance misuse, and disordered eating. The prevalence of each symptom was calculated. The false-negative rate (FNR) for step 1 identifying athletes that were positively screened on the subsequent step 2, was computed. Results: 65% players experienced the sport-related psychological distress while the prevalence of mental health symptoms ranged from 4.5% for substance misuse to 72.3% for alcohol misuse. Step 1 correctly detected all positive screened cases for anxiety, depression and suicidal ideation. In addition, a small proportion of cases were FNR for sleep disturbance (9.1%) and substance misuse (2.6%). 64.9% and 35.1% of cases were FNR for alcohol misuse and disordered eating, respectively. Conclusion: The SMHAT-1 might have acceptable performance in detect anxiety, depression, and suicidal ideation, however, it should be noted that false negatives also exist for other common mental health symptoms like disordered eating and sleep problems.